Analisis Serangan Penetration Testing: Sebuah Review Sistematik - Arya Kukuh Y; Geraldo Alfaren; indra gunawan (JIIFKOM (Jurnal Ilmiah Informatika dan Komputer), 2022)
In general, the penetration testing system process is often compared by junior system administrators to the system vulnerability assessment process. This mindset error has become a fatal error in managing computer system security. Vulnerability system assessment is a procedure for scanning for vulnerabilities in the system and filtering these weaknesses to avoid exploitation by hackers. This is clearly almost similar to the literal meaning of penetration testing which is the process of searching for vulnerabilities (weaknesses) and exploiting the system until the tester knows the real weak points of the system.